PENGARUH KEGIATAN EKSTRAKURIKULER ROHANI ISLAM (ROHIS) TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PAI - Nasihudin, Ade; Dewi, Sri Utami (THORIQOTUNA: Jurnal Pendidikan Islam, 2020)
This study aims to determine the effect of extracurricular activities ROHIS (Rohani Islam) on student achievement in Islamic education subjects at SDN 3 Cinagara Malangbong Garut. The research method that I use is a descriptive method with a quantitative approach. The population in this study were all participants / members of ROHIS at SDN 3 Cinagara Garut, totaling 30 students, and with a total sample of 30. Based on the calculation of the correlation between variables X and Y using the Rank Sperman formula (rs) of 0.58. The spherical rank correlation number is in the interval 0.41-0.60. With enough qualifications. This means that there is sufficient influence between ROHIS extracurricular activities on learning achievement in Islamic Education subjects at SDN 3 Cinagara. And through hypothesis testing it is known that the correlation number is significant. Because proven_count is 5.52 and ttable is 2.048. By comparing the two numbers, it is proven that tcount is greater than ttable. This contains an interpretation that the data regarding the effect of ROHIS Extracurricular Activities on Learning Achievement in Islamic Education Subjects at SDN 3 Cinagara are significant. Thus it is concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected.